Do monetary policy expectations influence transmission mechanism of Danish interbank market under the negative interest rate policy?. (2017) - Ito, Takayasu
In Denmark, monetary policy expectations have some impact on the interbank interest rates in the maturities of one, three and six months. The Danish central bank is successful, to some extent, in influencing the interbank interest rates in the maturities from one to six months through communication with financial markets. But the maturities from nine to 12 months are beyond their control. This fact indicates that market segmentation is observed in the short-term money market in Denmark. The ordinary transmission mechanism of interbank interest rates does not function because of the increased fluctuations in money market rates under a negative interest rate policy. It is therefore suggested that a negative interest rate policy presents complications that could limit policy effectiveness. Negative interest rate policy presents complications that could limit policy effectiveness.